THE USE OF INFORMATION TECHNOLOGY IN LEARNING ENGLISH - Mirkhodjayeva Mahliyo Islamovna; Bobokulova Gulrukh Sharipovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article is dedicated to the process of teaching English in a rapidly changing information society. The article gives the examples of use of modern information technology at the lessons of English and also its undeniable advantages. The authors in the article focus on the fact that it is necessary to learn foreign languages. The language is the main and the most effective mean of exchanging information among the people of our planet.